Serological Evidence of West Nile Virus in Wild Birds in Bangladesh - Ariful Islam; Shariful Islam; Mohammad Enayet Hossain; Jinnat Ferdous; Josefina Abedin; Mohammad Ziaur Rahman; Md. Kaisar Rahman; Md. Ahasanul Hoque; Mohammad Mahmudul Hassan (Veterinary Sciences, 2020)
West Nile Virus (WNV) is a vector-borne zoonotic disease maintained in a sylvatic cycle involving mosquito vectors and birds. To detect WNV and other flavivirus infections in wild resident and migratory birds, we tested 184 samples from 19 identified species within nine families collected during 2012–2016 from four districts in Bangladesh. We tested serum samples for the immunoglobulin G (IgG) antibody against WNV using competitive Enzyme-Linked Immunosorbent Assay (c-ELISA), whereas tracheal and cloacal swabs were subjected to consensus Polymerase Chain Reaction (c-PCR) for the detection of the flavivirus RNA. Overall, we detected 11.9% (n = 22; 95% CI: 0.07–0.16) samples were seropositive, including 15.9% in the migratory wild birds and 10.7% in the resident wild birds. The migratory wild Tufted duck showed 28.5% seropositivity, whereas the resident wild house crows showed 12.5% seropositivity. None of the swab samples was positive for flavivirus RNA infection (0%, n = 184; 95% CI: 0–0.019). These study findings recommend continued surveillance for early detection and to better understand the epidemiology of WNV and other flavivirus circulation in both birds and mosquitoes in Bangladesh.